Pengaruh Brand Love dan Brand Experience Terhadap Loyalitas Pelanggan pada Produk Glad2glow di Kota Malang - Sinta Ardelia; Rena Feri Wijayanti; Farida Akbarina (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aimed to analyze the influence of brand love and brand experience on customer loyalty toward Glad2Glow products in Malang City. Customer loyalty is an essential factor in maintaining business sustainability, particularly in the skincare industry, which is characterized by intense market competition. Therefore, companies need to understand the factors that contribute to building and sustaining customer loyalty. This study employed a quantitative approach using a survey method involving 100 Glad2Glow Moisturizer users selected through purposive sampling. The data were collected through questionnaires and analyzed with multiple linear regression with SPSS. The results indicated that brand love has a positive and significant effect on customer loyalty, Brand Experience also has a positive and significant effect on customer loyalty. Simultaneously, brand love and brand experience significantly influence customer loyalty. Future studies are recommended to include additional variables that may affect customer loyalty.